GLOS and HARM in patients with transient neurovascular symptoms with and without ischemic infarction - Förster, Alex; Ramos, Ana; Wenz, Holger; Böhme, Johannes; Groden, Christoph; Alonso, Angelika (Journal of neuroradiology, 2022)
Background and purpose - Gadolinium leakage in ocular structures (GLOS) on fluid attenuated inversion recovery images (FLAIR) is a novel imaging marker in acute ischemic stroke and other neurological disorders. - Methods - In patients with transient neurovascular symptoms who underwent repeated MRI with intravenous contrast agent administration, the presence of acute ischemic lesions on diffusion-weighted images (DWI) as well as the frequency and pattern of blood-brain barrier and blood-retina barrier impairment as demonstrated by the hyperintense acute reperfusion marker (HARM) and GLOS respectively on postcontrast FLAIR were evaluated. - Results - Overall 28 patients with transient neurovascular symptoms (median age 70.5 years; 18 (64.3%) male) were included. Follow-up MRI was performed within 35 (IQR 21-47) hours after the initial MRI. On DWI, acute ischemic lesions were observed in 22 (78.6%). On contrast-enhanced FLAIR, GLOS was observed in 12 (42.9%) patients: in 1 (3.6%) only in the anterior chamber, and in 11 (39.3%) in the anterior chamber and vitreous body. HARM was observed in 3 (10.7%) patients. In one patient without ischemic lesion on DWI or HARM on FLAIR, GLOS was observed in the anterior chamber and vitreous body. Presence of GLOS was associated with higher age (p=0.04) and detection of HARM (p=0.03). - Conclusions - In patients with transient neurovascular symptoms, GLOS is a frequent finding and associated with HARM on contrast-enhanced FLAIR. As GLOS was observed in one patient without an ischemic lesion or HARM, it might be useful as an additional imaging marker.